Rock and Pop Venues Acoustic and Architectural Design - Adelman-Larsen, Niels Werner (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Popular music plays a substantial role in most people's life. The demand and financial revenue of Rock and Pop concerts is large and still increasing with the decreased revenue on recorded music. Based on the first ever scientific investigations on recommendable acoustics for amplified music conducted by the author, this book sets forward precise guidelines for acoustical engineers to optimize the acoustics in existing or future halls for amplified music. Gives precise guidelines on how to design the acoustics in venues that present amplified music Debates essential construction details, including placement of sound system and use of possible building materials, in the architectural design of new venues or the renovation of old ones Portrays 75 well-known European Rock & Pop venues, their architecture and acoustic properties. 20 venues were rated for their acoustics by music professionals leading to an easy-to-use assessment methodology "Acoustics are important within pop and rock venues to ensure a great experience for audiences and performers. This book fills an important gap of knowledge on the acoustics of venues. It will be of value to sound engineers as well as building owners and operators and building design professionals". Rob Harris, Arup Acoustics "With this book, many future amplified music concerts will sound better, for the joy of audiences and musicians alike. This enormous work demonstrates a rare degree of passion and insight, from the hand of the key researcher in the field". Dr. Per V. Brüel.